Surgical treatment of rhinophyma using an ordinary bur - Kang, Jae Kyoung; Lee, Jae Seong; Choi, Jae Hyuck; Shin, Myoung Soo; Yun, Byung Min (Archives of craniofacial surgery, 2020)
Rhinophyma is a painless benign tumor of the skin of the nose. It is the most severe form of rosacea. Rhinophyma is particularly rare among Asians. It can be treated with surgical resection using various methods, including scalpel excision, dermabrasion, cryosurgery, argon laser, carbon dioxide laser, and electrocautery. However, the gold standard treatment of rhinophyma remains unknown. In the present case, we debulked a giant rhinophyma with a scalpel and contoured it using a bur. Along with a relevant literature review, we present a case of rhinophyma in an Asian patient who was treated at no additional cost using a bur widely used in general plastic surgery.Rhinophyma is a painless benign tumor of the skin of the nose. It is the most severe form of rosacea. Rhinophyma is particularly rare among Asians. It can be treated with surgical resection using various methods, including scalpel excision, dermabrasion, cryosurgery, argon laser, carbon dioxide laser, and electrocautery. However, the gold standard treatment of rhinophyma remains unknown. In the present case, we debulked a giant rhinophyma with a scalpel and contoured it using a bur. Along with a relevant literature review, we present a case of rhinophyma in an Asian patient who was treated at no additional cost using a bur widely used in general plastic surgery.